Gymnastics - Caine, Dennis John, 1949-; Russell, Keith, 1944-; Lim, Liesbeth (Chichester, West Sussex : Wiley-Blackwell, a John Wiley & Sons, Ltd., Publication, 2013)
"This new volume in the Handbook of Sports Medicine and Science series, published in conjunction with the Medical Commission of the International Olympic Committee, offers comprehensive and practical guidance on the training and medical care of competitive gymnasts. Written and edited by leading trainers, team doctors, coaches and other professionals with unparalleled experience in elite gymnastics, this book covers all the key aspects of caring for gymnasts, minimizing the unique risks these athletes face, and treating injuries when they happen. Individual chapters cover key topics such as energy needs and body weight management; biomechanics; psychology; the epidemiology of gymnastic injuries; treatment and rehabilitation of common injuries; injury prevention; and more. Endorsed by the International Gymnastics Federation (FIG), no other book offers such an in-depth look at the unique considerations and challenges that affect the growth, performance, training, and medical care of athletes in this demanding sport"--Publisher's description.
Part 1. Introduction -- The evolution of gymnastics / Keith Russell -- Part 2. Growth and development aspects -- Growth, maturation, and training / Adam D.G. Baxter-Jones -- Endocrinology / John S. Fuqua and Alan D. Rogol -- Skeletal health of gymnasts / Daniel Courteix, David Greene and Geraldine Naughton -- Energy needs and weight management for gymnasts / Jorunn Sundgot-Borgen, Ina Garthe and Nanna Meyer -- Part 3. Training and performance aspects -- Biomechanics related to injury / Gert-Peter Brueggemann and Patria A. Hume -- Biomechanics : Injury mechanisms and risk factors / Patria A. Hume, Elizabeth J. Bradshaw and Gert-Peter Brueggemann -- Gymnastics physiology / Neil Armstrong and N.C. Craig Sharp -- Gymnastics psychology / Thomas Heinen, Pia M. Vinken and Konstantinos Velentzas -- Part 4. Sport medicine aspects -- Epidemiology of injury in gymnastics / Dennis Caine and Marita L. Harringe -- Treatment and rehabilitation of common upper extremity injuries / Stephen Aldridge and W. Jaap Willems -- Treatment and rehabilitation of common lower extremity injuries / Liesbeth Lim -- Treatment and rehabilitation of common spine/trunk/head injuries / Larry Nassar -- Gymnastics injury prevention / Marita L. Harringe and Dennis J. Caine.
Edition statement from footnote citation on first page of each chapter.
Includes bibliographical references and index.
Description based on online resource; title from electronic title page (ebrary, viewed on March 4, 2015).
Keywords: Gymnastics; Gymnastics injuries; Gymnasts -- Health and hygiene; Sports medicine; Athletic Injuries; Gymnastics -- injuries; Gymnastics -- physiology; Sports medicine -- Handbooks, manuals, etc; Sports Medicine -- Handbooks; Sports medicine; MEDICAL -- Surgery -- General; Electronic books; Electronic books